Mudanças na dinâmica e na morfologia fluvial com aplicação do método stream power no trecho do rio Araguaia entre a cidade de Itacaiú (GO) e Cocalinho entre 2010 e 2019 - Souza, Chrystiano Alves de (2020)
This research was carried out in the stretch of the Araguaia river, covering the main course of the river between the cities of Itacaiú, Aruanã and Cocalinho, with the main objective of the research being the analysis of the evolution and the erosive / sedimentary morphological dynamics in the stretch defined in the middle basin from the Araguaia River, from 2010 to 2019, applying STREAMPOWER THEORY analysis models, for a period of nine years, based on remote sensing data and according to the methodology of Morais (2002). Along his journey, Morais carried out extensive research in 2002, in his master's dissertation, with the aim of quantifying and evaluating the morphological changes in the Araguaia River, in the 1960s and 1990s. In his research he proposed the analysis of attributes and features found along the river to map and identify the changes in the river that occurred during that period. One of the ways that Morais found to analyze the changes was the use of cartographic materials and satellite images to map the components of the river dynamics, later defined as morphometric and morphological environmental variables, active erosive and sedimentary processes, in order to diagnose, by means of of indices, the relationships between the erosive / sedimentary balance in the selected stretch. According to Morais, the results of these analyzes provide a diagnosis of the river's behavior through mathematical equations that make it possible to assess the intensity and predominance of these processes in the channel, but in a more in-depth analysis it was noticed that the methodology proposed by Morais achieves very beyond expected. However, the researches carried out using his method practically ended after his death in 2012, generating a period of approximately 22 years without data on the morphological alterations of the river that could be used to compare with the data obtained by him and to establish a historical panorama of the state of the Araguaia River. Thus, it was proposed to continue the application of its method in a section of the Araguaia river defined as segment 5, as it is the segment that borders the city of Aruanã, where intense changes in the main channel have been identified, the implementation of the cargo port. being an activity that generates many impacts on the morphology of the river, and because it is a stretch where other research by the author has already been carried out. To carry out this research, satellite images obtained in the years 2010 to 2019 were used, following the cartographic rigors in order to create a temporal retrospect with the Morais data and perform the Cartographic Reambulation of the data obtained from the Remote Sensing. But the research did not stop at these analyzes. With it, it was possible to determine an Equilibrium Relationship of the river, from the data obtained and the application of the Stream Power method, which analyzes the erosive potential of a channel or a river that naturally has a very intense dynamics, in the search to reach the balance and stability between erosive / depositional agents. According to what was expected and in accordance with the Morais data, the results showed an increase in sedimentary deposits, mainly in the parameter of lateral sand bars and a decrease in the quantity and areas of islands and remaining islands, which are being attached to the river plain. Indicating that in this stretch of the Araguaia River the sedimentary process is more active, especially in regions where it is at a more advanced stage.